2011
DOI: 10.1111/j.1440-1681.2010.05469.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain angiotensin AT1 receptors as specific regulators of cardiovascular reactivity to acute psychoemotional stress

Abstract: 1. Cardiovascular reactivity, an abrupt rise in blood pressure (BP) and heart rate in response to psychoemotional stress, is a risk factor for heart disease. Pharmacological and molecular genetic studies suggest that brain angiotensin (Ang) II and AT(1) receptors are required for the normal expression of sympathetic cardiovascular responses to various psychological stressors. Moreover, overactivity of the brain AngII system may contribute to enhanced cardiovascular reactivity in hypertension. 2. Conversely, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 127 publications
(256 reference statements)
1
17
0
1
Order By: Relevance
“…Alignment of these changes in response to angiotensin I and angiotensin II indicates that the process of response to angiotensin II at the receptor's level and or mediation in response at the receptor or post-receptor levels may be affected by garlic powder. Also angiotensin II in addition to vessels can change blood pressure and heartbeat by affecting the central nervous system (24,36). This part of the findings is confirmed by garlic's effects on arterial blood pressure in normotensive and hypertensive animals.…”
Section: Discussionsupporting
confidence: 70%
“…Alignment of these changes in response to angiotensin I and angiotensin II indicates that the process of response to angiotensin II at the receptor's level and or mediation in response at the receptor or post-receptor levels may be affected by garlic powder. Also angiotensin II in addition to vessels can change blood pressure and heartbeat by affecting the central nervous system (24,36). This part of the findings is confirmed by garlic's effects on arterial blood pressure in normotensive and hypertensive animals.…”
Section: Discussionsupporting
confidence: 70%
“…However, AT 1 receptors are localized not only in areas related to the regulation of autonomic and endocrine control, but also in many other areas of the brain responsible for emotional, sensory and motor functions. For example central Ang II through AT 1 receptors may be a specific brain modulatory factor in the control of the reaction to stress (Mayorov, 2011;Saavedra et al, 2011). Stress can affect not only the hormonal and cardiovascular system, but also the gastric mucosal integrity and can initiate gastric mucosal damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that alteration in a single acute stress response event can predict future cardiovascular disease risk (Chen et al, 2007), such as stroke (Jern et al, 1989) and hypertension (Kohan and Padilla, 1994). Acute stress can trigger autonomic and neuroendocrine-mediated changes in cardiac contractility and peripheral vascular resistance (Reich et al, 1981) and involves vasoactive mediators such as plasma endothelin (ET-1) (Fujii et al, 2005; Kaehler et al, 2002), angiotensin II (Mayorov, 2011) and corticosterone (Taniyama and Griendling, 2003; Treiber et al, 2000). …”
Section: Mechanisms Contributing To Els-induced Cardiovascular Dysmentioning
confidence: 99%
“…In this regard, the hypothalamic- pituitary-adrenocortical (HPA) system and the sympathetic nervous system (SNS) have received special attention. In addition, it has been shown that several vasoactive peptides such as vasopressin, endothelin-1 and angiotensin II are released secondary to behavioral stimuli, exerting amplificatory effects in cardiovascular reactivity (Aguilera and Rabadan-Diehl, 2000; Loria et al, 2010b; Mangiafico et al, 2002; Mayorov, 2011; Spieker et al, 2002; Treiber et al, 2000). Cardiovascular reactivity reflects an enhanced response in blood pressure, heart rate or other hemodynamic parameters to secondary stressors (Manuck & Krantz, 1985).…”
Section: Introductionmentioning
confidence: 99%